An economic evaluation of diabetes mellitus in India: A systematic review. Issue 11 (November 2022) - Sathyanath, Shreyaswi; Kundapur, Rashmi; Deepthi, R.; Poojary, Santhosh N.; Rai, Sathvik; Modi, Bhavesh; Saxena, Deepak
Abstract: Background: Approximately 88 million people throughout Southeast Asia have diabetes, of which 77 million reside in India. India had an annual estimated diabetes treatment cost of Rs.10, 000 to 12, 000 crore in 2003, which is likely to rise to as high as Rs. 1, 26, 000 crores by 2025. Aim: To assess the annual mean expenditure for an individual with diabetes mellitus. Methods: We used search terms and Boolean operators to identify studies on the economic burden of diabetes mellitus patients in India between 2015 and 2020. Thereafter, we used the checklists of STROBE, as well as the PRISMA, Drummonds and down, and Black criteria, to assess the quality of included studies. Then, Meta xl was used to calculate the weighted means and weighted proportion based on the quality assessment findings. Results: Mean expenditure with a maximum weightage of 100% was found in a community-based study, whereas the lowest weightage obtained was 20%. The mean expenditure on diabetes and its complications was calculated as INR 15, 535/-(USD 209.3) per year, with a pooled mean of INR 17, 080(USD 230.1)per year. On average, the OPD charges were 3%–5% of the total annual income of the individual. However, when there were complications and hospitalization, the average expenditure was higher (21%) which averages to around 11, 000 INR. Conclusions: While patients spent 3% of their annual income on only OPD charges on average, complications substantially increased the total cost by more than 10%, which amounts to catastrophic health expenditure. Highlights: This systematic review includes community-based studies, hospital-based studies and a model development study. There was a catastrophic health expenditure increase of ˃10% among hospitalised patients and those with diabetes-related complications.